That's not me [videorecording (DVD)] - Foulcher, Alice; Lucas, Isabel, 1985-; Davies, Richard (Shoreline Entertainment, 2026)
"Polly's dreams of making it as an actor are crushed when her identical twin sister lands a coveted role on an HBO show. At first resentful about being mistaken for her sister at every turn, she soon succumbs to taking advantage of her sibling's newfound celebrity, but Polly's indulgence in free swag, comped drinks, and casual sex with gorgeous famous men have life-changing consequences for them both."--